2005
DOI: 10.1093/carcin/bgi224
|View full text |Cite
|
Sign up to set email alerts
|

The time and spatial effects of bystander response in mammalian cells induced by low dose radiation

Abstract: Bystander effects induced by low dose of ionizing radiation have been shown to widely exist in many cell types and may have a significant impact on radiation risk assessment. Though many studies have been reported on this phenomenological observation, the mechanisms underlying this process are not clear, especially on the questions of how soon after irradiation the bystander effects can be initiated and how far this bystander signal can be propagated once it is started. DNA double-strand breaks (DSBs) induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
123
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(139 citation statements)
references
References 38 publications
16
123
0
Order By: Relevance
“…Frequency histograms (Figure 2b) illustrate that this is a general increase, rather than being limited to a subset of cells. It is also interesting to note that there was a similar increase in SCE frequency for both the 1:100 and 1:1000 dilutions, which is consistent with previous reports that the BSE appears to operate by an 'on/off' mechanism (Nagasawa and Little, 1992;Deshpande et al, 1996;Hu et al, 2006). Therefore, only the 1:100 dilution cell transfer method was utilized in subsequent experiments.…”
Section: Resultssupporting
confidence: 86%
“…Frequency histograms (Figure 2b) illustrate that this is a general increase, rather than being limited to a subset of cells. It is also interesting to note that there was a similar increase in SCE frequency for both the 1:100 and 1:1000 dilutions, which is consistent with previous reports that the BSE appears to operate by an 'on/off' mechanism (Nagasawa and Little, 1992;Deshpande et al, 1996;Hu et al, 2006). Therefore, only the 1:100 dilution cell transfer method was utilized in subsequent experiments.…”
Section: Resultssupporting
confidence: 86%
“…Assuming that SCEs generated in bystander cells likewise result from HRR events, it seems unlikely this process involves directly induced ("frank") DNA DSBs as previously suggested [28,29]. The chromosome aberration and mutation spectra observed in bystander cells support our hypothesis that single-stranded oxidative lesions are the source of HRR-derived SCEs in S-phase cells.…”
Section: Introductionsupporting
confidence: 85%
“…The difference in the extent of this reduction between MMC and low dose α-particle exposures is likely related to the types and levels of DNA damage induced by these agents and specific repair systems employed to resolve this damage. It also must be noted that all cells are exposed in MMC-treated cultures whereas in the case of low dose α-particle irradiations, only a small percentage of cells are directly irradiated (≀2%) and a portion of non-irradiated cells may not be exposed to bystander molecules as a result of the limited diffusion potential of these signaling factors through gap-junction mediated intercellular communication (GJIC) or the cell culture medium [25,29,54].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated that ROS is very important for the induction of RIBE (reviewed by Azzam et al, 2004). Our previous studies (Hu et al, 2005(Hu et al, , 2006) also indicate that ROS is an important mediator for the induction of DSBs in non-irradiated cells. Furthermore, by treating medium donor cells with dimethyl sulfoxide, a quencher of ROS, before irradiation could effectively reduce the DIA of conditioned medium (Han et al, accepted).…”
Section: Discussionmentioning
confidence: 90%
“…In our previous studies, based on the immunochemistry of phosphorylated form of H2AX (g-H2AX), a reliable marker to reflect the induction of DNA double strand breaks (DSBs) in cellular nucleus (Rothkamm and Lobrich, 2003;Sedelnikova et al, 2002Sedelnikova et al, , 2004, we demonstrated that in situ visualization of DSBs could be used to assess the early events of radiation-induced extranuclear/extracellular (bystander) effects (Hu et al, 2005). In addition, the bystander DSBs were induced in a time-dependent manner and could be detected as early as 2 min post-irradiation (Hu et al, 2006). However, the nature of these intercellular signaling molecule(s) and how they participate in initiating radiation-induced bystander effects (RIBE) are not clear.…”
mentioning
confidence: 99%